Fenomena Second Account Oleh Mahasiswa Pada Media Sosial Instagram - Salma M, Jihan; Noor Rakhmad, wiwid; Bayu Widagdo, Muhammad (Interaksi Online, 2024)
Instagram can be said to be a medium for displaying activities related to daily life such as uploading photos during holidays, when doing activities such as cooking and so on, or they can even upload things such as quoting words, songs and so on. The aim of this research is to find out the meaning of a second Instagram account for students. The data collection technique used in qualitative research is by using observation techniques, interviews. The results of this research are that users of the second account on the Instagram platform have the same goal, namely maintaining and connecting with friends or close friends from thereal world. They use second accounts in unique ways to maintain interpersonal relationships, especially by selecting the private feature to have control over who can become a follower. The friendship relationship in the second account is characterized by reciprocity and acceptance. Users use the second account as a comfort zone to share without worrying about judgment or hurt feelings from their followers. Second account users on the Instagram platform have the same goal, namely maintaining and connecting with friends or close friends from the real world. They use second accounts in unique ways to maintain interpersonal relationships, especially by selecting the private feature to have control over who can become a follower. The friendship relationship in the second account is characterized by reciprocity and acceptance. Users use the second account as a comfort zone to share without worrying about judgment or hurt feelings from their followers